(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2022)
This article describes the lexical and semantic relation of hyponyms in English linguistics, which means that analyzing deeply the features of hyponyms and its characteristic features. One of the most vital progresses in cognitive understanding of information, one of the extremely significant devices to classifying vocabulary and performing of the human perception. Lexical and semantic relations of hyponyms are taken into consideration important when giving logical meaning and connection to speech that help to express the meaning of the word.